Origins and Conceptual Principles of the International Studio Glass Movement: Ukrainian and International Context - Bokotey, Mykhaylo (HUDPROM: The Ukrainian Art and Design Journal, 2024)
The article deals with one little-studied phenomenon in Ukrainian art history – the international studio glass movement that began in the 1960s in the United States and Europe. Subsequently, the movement spread to all countries where glassmaking was a well-developed traditional craft. The article describes the history of the emergence and spread of this artistic phenomenon initiated by American and European artists and informs about the movement’s followers in the Ukrainian art scene. It is noted that the artists A. Bokotey and F. Cherniak actually simultaneously and independently of their foreign colleagues, formed the basis for the Ukrainian studio glass traditions. At the same time, the article reveals the conceptual foundations and principles of the studio movement and considers the key trends. It proposes a specific system of style characteristics based on the analysis of the works of leading contemporary glass artists. At the time when Ukrainian art criticism is only beginning to discuss the need to revise certain concepts and definitions given the changes caused by the international studio movement, the world’s academic circles are discussing the gradual completion of this artistic phenomenon and the emergence of post-studio trends. The younger generation of glass artists, following the trends of conceptual art practices prevalent in contemporary visual culture, is forming new trends in artistic expression. At the same time, the artists position glass as the primary medium of creative narrative in their author’s search, thus remaining at the forefront of the new artistic glassmaking movement. Based on the study’s results, the article draws several vital conclusions that substantiate the reasons for the spread of the international studio glass movement and its impact on changes in contemporary decorative art. It is emphasized that Ukrainian artists, institutions, and projects that stimulate the development of glass art occupy a significant place on the world stage and significantly impact global international processes.